APPRECIATING COVERS - Magnus, Cristyn; Magnus, P.D.; Uidhir, Christy Mag; Mcclamrock, Ron (The Nordic Journal of Aesthetics, 2022)
A recording or performance of a song is a cover if there is an earlier, canonical recording of the song. It can seem intuitive to think that properly appreciating a cover requires considering it in relation to the original, or at least that doing so will yield a deeper appreciation. This intuition is supported by some philosophical accounts of covers. And it is complicated by the possibility of hearing in, whereby one hears elements of the original version in the cover. We argue that it can nevertheless be just as legitimate to consider a cover version on its own as it is to consider it in relation to the earlier recording that it is covering. In some cases, these two modes of appreciation will offer distinct rewards. In other cases, one mode will be substantially more rewarding than the other. The details matter, especially in complicated cases like covers of covers, but neither mode is privileged in principle.